2009
DOI: 10.3113/fai.2009.0955
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparative Study of the Scarf and Ludloff Osteotomies in the Treatment of Hallux Valgus

Abstract: Overall the patients who had a scarf osteotomy had a superior outcome at 6 and 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 29 publications
(33 reference statements)
3
29
1
3
Order By: Relevance
“…Significant loss of correction of the intermetatarsal angle early in the postoperative period has been reported (Robinson et al, 2009), and it is interesting that in one study led to a recurrence in 26,7% of the patients (Chiang et al, 2012). Malunion requiring revision has also been observed with a reported incidence of 1.5 % to 5%.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 3 more Smart Citations
“…Significant loss of correction of the intermetatarsal angle early in the postoperative period has been reported (Robinson et al, 2009), and it is interesting that in one study led to a recurrence in 26,7% of the patients (Chiang et al, 2012). Malunion requiring revision has also been observed with a reported incidence of 1.5 % to 5%.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…A C C E P T E D M A N U S C R I P T 4 union is a well described complication with an incidence of 2%-6,7% (Chiang et al, 2012;Chiodo et al,2004;Robinson et al, 2009;Trnka et al, 2008). Significant loss of correction of the intermetatarsal angle early in the postoperative period has been reported (Robinson et al, 2009), and it is interesting that in one study led to a recurrence in 26,7% of the patients (Chiang et al, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many investigators have reported the use of these successful metatarsal osteotomies for HV deformity for many different indications. Robinson et al [8], Saragas et al [9] and Adam et al [10] reported successful and differing proximal osteotomy techniques for moderate to severe HV. Bai et al [11] reported a series of effective distal metatarsal osteotomies for 76 moderate to severe HV deformities, with a very low incidence of complications.…”
Section: Introductionmentioning
confidence: 99%